THE EFFECT OF FOOTSTEP STRATEGY UPON STUDENTS’ DESCRIPTIVE WRITING ACHIEVEMENT OF THE SEVENTH GRADE STUDENTS OF SMP N 5 SINGARAJA IN THE ACADEMIC YEAR 2015/2016 - TRIANA JULIARI, I GUSTI AYU INDAH (Widya Accarya, 2015)
AbstractÂ Â Â Â Â Â Â Â Â Â Â Â  The recent study aims at investigating the effect of using â??Footstep Strategyâ? upon the studentsâ?? descriptive writing achievement of the seventh grade students of SMP Negeri 5 Singaraja in the academic year 2015/2016. To acquire the above aim of the study, a posttest only control group design was taken as the research design of the present study. The study took place in SMP N 5 Singaraja. The population was all the seventh grade students of SMP N 5 Singaraja. Based on the result of cluster random sampling, the researcher took class VIIB and VIIC as the sample of the study. Class VIIB was determined as the experimental group and VIIC as the control group. Both groups consisted of 36 students. The students of experimental group were taught to write with the guidance of â??Footstep Strategyâ?, while the control group was taught by â??conventional writing techniqueâ?. At the end of the experimental period, the groups were given a posttest. The result of the data analysis showed that students who were taught by using the Footstep Strategy performed better achievement that those who were taught by implementing conventional writing technique. It was shown from the mean score of the experimental group which was 75.19 and the mean score of control group was 65.00. Moreover, the result of t-test analysis showed that the to was 5.000. It was higher than the value of tcv at 1.96 (Î±=0.05). It indicated that the difference between the two groups was significant. In this case, the null hypothesis was rejected. In other words, there is a significant difference in the writing achievement of the seventh grade students of SMP N 5 Singaraja taught by using footstep strategy and those taught by using conventional writing technique.Â Keywords: Footstep strategy, descriptive writing, studentsâ?? writing achievement.